Risk and prognostic factors for SARS-CoV-2 infection in Spanish population with multiple sclerosis during the first five waves - Pilo De La Fuente, Belén; González Martín-Moro, Julio; Martín Ávila, Guillermo; Méndez Burgos, Alejandro; Ramos Barrau, Laura; Thuissard, Israel; Torrejón Martín, Marta; Aladro Benito, Yolanda (Frontiers in Neurology, 2022)
BACKGROUND. Data of COVID-19 incidence in multiple sclerosis (MS) patients during the first wave have been published, but are scarce for the remaining waves. Factors associated with COVID-19 infection of any grade are also poorly known. The aim of this study is to analyze the incidence, clinical features and risk factors for COVID-19 infection of any grade in patients with MS during waves 1 to 5. METHODS. This study prospectively analyzes the prevalence of COVID-19 from the 1st to the 5th wave by periodic case ascertainment in MS patients followed at the University Hospital of Getafe. Global and stratified cumulative incidence was calculated. Logistic regression models were used to estimate the weight of selected variables as risk and prognostic factors. RESULTS. We included 431 patients with MS, of whom 86 (20%) were infected with SARS-CoV2. The overall cumulative incidence of confirmed cases was similar to that of Madrid (13,689 vs. 13,307 per 100,000 habitants), but 3 times higher during the first wave and slightly lower from the 2nd to the 5th waves. The majority (86%) of MS patients developed mild forms of COVID-19. Smoking was the only factor associated with SARS-CoV2 infection of any grade (OR 0.491; 95% CI 0.275-0.878; p=0.017). Risk factors associated with severe forms were EDSS ≥3.5 (OR 7.569; 95% CI 1.234-46.440) and pulmonary disease (OR 10.763; 95% CI 1.27-91.254). CONCLUSIONS: in this MS cohort, the incidence of COVID-19 was similar than in general population. Smoking halved the risk of being infected. Higher EDSS and pulmonary comorbidity were associated with increased risk of severe forms.